Makna Amar Dan Nahi Dalam Surah An-Anisa Ayat 36 - Alwi Gorga Doli Harahap; Hadid Alnusa; Pimpinan Abaik Simamora (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The purpose of this article is to analyze the meaning of Amar and Nahi in Surah An-Nisa verse 36. This discussion focuses on the meaning of Amar and Nahi in Q.S An-Nisa verse 36. The author chose Surah An-Nisa verse 36 because it contains Amar's rule. and Nahi in relation to the Divinity of Allah. Where in the An-Nisa letter there are the words. تشركوا وال هللا واعبدوا In the results of this research, the author uses a qualitative method, namely a learning method using reading verse 36 of the An-Nisa Letter. Next, we will briefly explain this section, focusing on the study of the meaning of amar and nahi in the Koran surah an-nisa verse 36. And to complete this research, the author used one source of information, namely secondary sources. We as authors have collected several reference book related to the debate discussed and researched. To find out what the author found, the meaning of amar and the meaning of nahi, we need to know: (1) Who issued the warning and to whom it was addressed; (2) What is the purpose of the warning? (3) In what cases is the warning issued? So, amr is Allah's command which must be carried out by believers in accordance with the commands of the Qur'an, and nahi is linguistically the opposite of amar, and according to terminology, nahi is an expression that requires an action to be carried out. This means that there is pronunciation by people in a higher position to "people in a lower position", which is expressed more simply in the ulum of the Qur'an, namely the obligation to abandon an action or prevent the carrying out of a certain work, and the nahi contained in the surah. An-Nisa verse 36 Nahi Standards in the form of requirements